How Action Research can enhance knowledge transfer and university-industry cooperation. - López-Paredes, Adolfo; De-la-Varga-Salto, José María; Galindo-Reyes, Fuensanta Carmen; González-Varona, José Manuel (Springer, Cham, 2026)
We have found that universities are not making full use of their strengths to fulfil their knowledge transfer function. Since the implementation of the European Bologna reform of higher education, internships have played a central role both, in undergraduate and graduate degrees. One of the first results of this has been an increase in the number of final projects that students have completed in companies. We believe that this should be recognised as a key strength and exploited to substantially increase the number of collaboration agreements between universities and enterprises in research and development and innovation. In this paper, we argue that bachelor's and master's theses developed by students in companies would have an impact on the third mission of universities if they were managed adequately. Our research focused on Management and Industrial Engineering studies at Spanish universities. We found that Action Research (AR) is rarely used in final undergraduate or postgraduate projects, regardless of whether the projects were carried out during internships or proposed by companies. However, it is quite commonly used in universities in Central and Northern Europe. We propose a simple AR model for managing projects carried out by undergraduate and postgraduate students in collaboration with companies. The model has been validated using the bachelor's thesis of three Industrial Management students at the University of Málaga. Transfer activities are centred on students in this model, who are positioned as the nexus between company tutors and university directors.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Cooperación científica y técnica; Cooperación universidad empresa; Action research; Action learning; Knowledge transfer; Third mission